2021
DOI: 10.3126/jngs.v62i0.38697
|View full text |Cite
|
Sign up to set email alerts
|

Geology and sedimentary environment of the Surma Group of rocks, Bandarban anticline, Bandarban, Bangladesh

Abstract: The study illustrates the effect of tectonics, climate, and relative sea-level change on the depositional process of the Miocene Bhuban and Boka Bil Formation of Bengal Basin. Outcrop sediments of five transverse sections exposed along the axial zone of Bandarban anticline were studied. Twelve lithofacies such as Gm, Gms, Sm, ST, Sp, Sr, Sl, Sf, Sll, Fw, Fl and Fm have been identified within the successions and grouped into (i) turbidite generated, (ii) outer fan distal lobe basin plain and (iii) tide-influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…The Bengal Basin is situated where the Indian plate, the Tibetan (Eurasian plate), and the Burmese sub-plate meet (Haque and Roy, 2021). Various tectonic events within the Indian plate have caused differences in the basin fill history among the geotectonic provinces (Alam et al, 2003).…”
Section: Geological Setting and Physiographymentioning
confidence: 99%
“…The Bengal Basin is situated where the Indian plate, the Tibetan (Eurasian plate), and the Burmese sub-plate meet (Haque and Roy, 2021). Various tectonic events within the Indian plate have caused differences in the basin fill history among the geotectonic provinces (Alam et al, 2003).…”
Section: Geological Setting and Physiographymentioning
confidence: 99%
“…The Upper part of the Bhuban Formation is considered the submarine fan deposit (Roy et al, 2006). Then the Boka Bil Formation was deposited dominantly under the estuary to tidal flat environment and sometimes the depositional environment shifted from a continental slope to a marginal shallow marine environment (Haque and Roy, 2021). The Surma Group mainly comprises sandstone, siltstone, silty shale, and shale throughout both flanks of the anticline.…”
Section: Introductionmentioning
confidence: 99%
“…This asymmetric open-folded structure exhibits a double plunge, and Neogene succession concurred progradation sequences from deep marine to fluvial deposits followed by shallow marine events 9 , 10 . Descriptive outcrop sediments of the Bandarban structure were studied to evaluate the impact of tectonics, climate, and transgressional and regressional events on the depositional settings 11 , 12 . Jaldi, Dakhin Nhila, and Inani structures have moderate amplitude, and seismic studies indicated the possibility of restraining from the fold initiation 13 .…”
Section: Introductionmentioning
confidence: 99%